Spontaneous Rupture of Abdominal Aorta after Seizure in a 23-Year-Old Woman: A Case Report. Issue 2 (March 2014) - Paik, JH; Jung, HM; Yun, SH; Lee, JS; Han, SB; Kim, JS; Kim, JH
Spontaneous non-aneurysmal aortic rupture is a rare and life threatening clinical entity. A 23-year-old female patient who visited a nearby hospital due to intractable seizure was transferred to our hospital with the impression of hypotension and decreased level of haemoglobin. She had a history of seizure attacks once a month. However, in the 2 weeks before presentation, the frequency of seizure attacks had increased to 2 to 3 times a day. An abdominal-pelvic computed tomogram scan showed extravasation of contrast from the abdominal aorta at L3 level. An emergency laparotomy revealed a 0.3 cm diameter tear in the posterior wall of the aorta, superior to the iliac bifurcation. We discuss the mechanism of spontaneous aortic rupture and the possibility of aortic rupture related to seizure attacks. (Hong Kong j.emerg.med. 2014;21:103-106)